Aspects of the sociality, ecology, reproductive biology and genetic relatedness of colonies of the highveld molerat, Cryptomys hottenetotus pretoriae - Bennett, Nigel Charles (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2007.